2017
DOI: 10.4067/s0717-73562017005000016
|View full text |Cite
|
Sign up to set email alerts
|

Percutores Líticos De La Pampa Del Desierto De Atacama (Norte De Chile): Tecnología, Huellas De Uso, Decoración Y Talladores

Abstract: Podría decirse que la lítica es el material por excelencia en los estudios de cazadores recolectores en arqueología. Paradójicamente es muy poco lo que sabemos acerca de los artefactos involucrados en los procesos de producción de los instrumentos líticos, menos aún de los percutores duros, utilizados preferentemente en las etapas iniciales de su cadena operativa. Presentamos el análisis de un conjunto de percutores hechos sobre guijarros que forman parte de un extenso taller lítico ubicado en la pampa de Anto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
0
9
0
5
Order By: Relevance
“…It has been suggested that this spatial configuration of the Southern Atacama lithic landscape was part of a broader regional pattern, within which the siliceous deposits, located at an average distance of 80 km from the coast, form an extensive system of approximately 800 km throughout northern Chile's Central Valley [48]. Techno-functional and lithic reduction sequence analyses carried out in both coastal and interior prehistoric contexts support this idea, by signaling the presence of primary exploitations of chert nodules in the Central Depression and a marked predominance of small-sized flakes, mostly with no cortex, in the coastal assemblages [46][47][48]50,52,96].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that this spatial configuration of the Southern Atacama lithic landscape was part of a broader regional pattern, within which the siliceous deposits, located at an average distance of 80 km from the coast, form an extensive system of approximately 800 km throughout northern Chile's Central Valley [48]. Techno-functional and lithic reduction sequence analyses carried out in both coastal and interior prehistoric contexts support this idea, by signaling the presence of primary exploitations of chert nodules in the Central Depression and a marked predominance of small-sized flakes, mostly with no cortex, in the coastal assemblages [46][47][48]50,52,96].…”
Section: Discussionmentioning
confidence: 99%
“…[53,54]. It is in these large detritus flows that locations of chert primary exploitation are most commonly recorded across the Southern Atacama [46,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por el contrario, reconocemos que es sumamente común a lo largo del litoral al menos desde el norte de la desembocadura del río Loa hasta el sur de Taltal dentro del lapso temporal comprendido entre los 6500 y 4000 cal. a.p., emplazadas especialmente junto a aguadas y bahías abrigadas (Ballester et al 2014a;2014b;2017;Bittmann 1984;Castro et al 2016;Contreras et al 2008;Llagostera 1989Llagostera , 2013Mostny 1964;Núñez et al 1974;Salazar et al 2015;Zlatar 1983Zlatar , 1989. Las similitudes constructivas y de planificación infraestructural en la edificación son notables, conformando una misma tradición cultural que excedía la esfera arquitectónica y espacial también hacia el ámbito de las tecnologías de pesca y caza marina, con diseños, estrategias y dispositivos comunes (Ballester y Gallardo 2011;Ballester et al 2017;Llagostera 1989).…”
Section: Detail Of Skeletal Elements Presents (In Red) In Every Indivunclassified